2020
DOI: 10.1016/s2542-5196(20)30221-7
|View full text |Cite
|
Sign up to set email alerts
|

People-centred surveillance: a narrative review of community-based surveillance among crisis-affected populations

Abstract: Outbreaks of disease in settings affected by crises grow rapidly due to late detection and weakened public health systems. Where surveillance is underfunctioning, community-based surveillance can contribute to rapid outbreak detection and response, a core capacity of the International Health Regulations. We reviewed articles describing the potential for community-based surveillance to detect diseases of epidemic potential, outbreaks, and mortality among populations affected by crises. Surveillance objectives h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Detailed case studies of cholera outbreaks provide practical observations on the mechanisms of surveillance, diagnosis, and response which can reduce delays. Early detection with high-quality epidemiological data has been augmented with the use of sentinel site surveillance at hospitals equipped with RDTs and trained and vigilant health workers in Kathmandu, Nepal [ 162 ]; community-based surveillance using existing community health worker or Red Cross volunteer networks to enable early warning of clusters in the community before patients appear at health facilities in Central African Republic and Haiti [ 71 , 152 , 182 , 183 ]; and other event-based surveillance mechanisms, including phone hotlines and mobile phone fleets, to enable immediate notification of suspect events in public, private, and NGO clinics and in the community, as seen in Northern Nigeria and Cameroon [ 171 , 184 , 185 ]. Response should not be delayed by poor laboratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed case studies of cholera outbreaks provide practical observations on the mechanisms of surveillance, diagnosis, and response which can reduce delays. Early detection with high-quality epidemiological data has been augmented with the use of sentinel site surveillance at hospitals equipped with RDTs and trained and vigilant health workers in Kathmandu, Nepal [ 162 ]; community-based surveillance using existing community health worker or Red Cross volunteer networks to enable early warning of clusters in the community before patients appear at health facilities in Central African Republic and Haiti [ 71 , 152 , 182 , 183 ]; and other event-based surveillance mechanisms, including phone hotlines and mobile phone fleets, to enable immediate notification of suspect events in public, private, and NGO clinics and in the community, as seen in Northern Nigeria and Cameroon [ 171 , 184 , 185 ]. Response should not be delayed by poor laboratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…All epidemics reviewed here occurred in identified cholera hotpots in Sub-Saharan Africa [ 21 ], which have documented weak surveillance systems [ 34 ], low coverage of WASH services [ 35 ] and high global acute malnutrition (GAM) prevalence (2.7%, 6.1%, and 8.10% in Malawi, Mozambique and DRC, respectively [ 36 ]), which all increase risk and severity of outbreaks. Additionally, presence of armed conflict and population displacement likely exacerbated V. cholerae transmissibility and case fatality among symptomatic cases, as demonstrated by other research documenting the overlap between crises and cholera epidemics [ 37 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most case studies described here, epidemics were confirmed but the methods were not specified. Additionally, our data indicated that epidemiological data were often inaccurate or incomplete: reliance on under-resourced surveillance systems may have led to the data delays in the alert, delayed confirmation and delays to the resulting response [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological surveillance is an expected measure to be undertaken in a pandemic (Holmes et al, 2018; Thomas, 2014) but COVID‐19 also enabled other forms of surveillance to be exercised (Eck & Hatz, 2020; Wenger et al, 2020). Examples include technological surveillance using contact tracing apps (Shaw et al, 2020; Sonn & Lee, 2020), community‐based surveillance through systematic community reporting especially in hard‐to‐reach regions (Ratnayake et al, 2020), and security surveillance via increased uniformed presence (Chretien et al, 2007; Kalkman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%